Investigation of anxiety of swimmers regarding contracting new typ of Coronavirus (COVID-19) - Batu, B.; Aydin, D. (International Refereed Academic Journal of Sports, Health and Medical Sciences, 2020)
Aim: In this study, it was aimed to investigate that anxiety of Swimmers about contracting new type of Coronavirus (Covid19). Method: Swimmers in active state in Turkish Swimming Federation participated in this study. The participants of this research consist of 247 female and 203 male swimmers (450 in total) who are in active state in Turkish Swimming Federation. In this study, "Personal Info Questionare" and "Anxiety of atheletes for contracting new type of Coronavirus (Covid-19) scale" developed by Demir et al. (2020) were used as data collection tool. Results: Differences between sex and personal anxiety sub-dimension and general differences were determined. Differences between in personal anxiety and anxiety regarding socializing both in sub-scale and overall were determined. There is no difference reported according to factors such as financial status based on minimum wage, having a chronic disease, the best swimming style, making practice at home during pandemic. Conclusion: It was concluded that, swimmers have higher level of anxiety of contracting new type of Coronavirus (Covid-19) than the medium level in this study